Typically active ocular toxoplasmosis: a case report - Priscilla Dwianggita (DiscoverSys Inc., 2020)
Background: Ocular toxoplasmosis, a potentially blinding and non-curable disease with a progressive and relapsing course, is the most common cause of infectious posterior uveitis. Infection may be congenital or acquired through ingestion of uncooked meat, contaminated vegetables, or water of different parasite Toxoplasma gondii. Case Presentation: We report a case of a 58-year-old female who came with blurred vision and floaters in her left eye for a month. She had contact with cats, birds, and dogs, as well as eaten raw food before. On examination, anterior segments were normal with visual acuity of 6/6 in the right eye and 6/9 in the left eye. Fundus examination revealed a vitreous haze with a yellow-white exudate located between pupil and macula. Since the disease's progress may lead to recurrence and potential blindness, it must be recognized clinically, and treatment should be started as early as possible, especially in the active period. Our patient was treated with oral trimethoprim (160 mg)/sulfamethoxazole (800 mg) twice daily and topical eye drops of prednisone four times daily on the left eye. These drugs were prescribed instead of sulfadiazine/pyrimethamine, which is classical and standard therapy. After 4 weeks, the fundus examination showed the toxoplasmic lesion was significantly decreased in size, and vitreous haze was improved.Conclusion: Trimethoprim-Sulfamethoxazole regiments as the alternative option for active ocular toxoplasmosis also shows significant improvement with less adverse effect.